BUSINESS PERFORMANCE OF WOMEN ENTREPRENEUR: A SYSTEMATIC LITERATURE REVIEW - Noorazlina Ahmad; Mohamad Hanif Baharudin; Mohd Khairi Ismail (Journal of Islamic, Social, Economics and Development, 2024)
Most entrepreneurs venture into MSMEs as their first step to run a business. Entrepreneurship is increasingly being recognised by an economist and management scholars as a possible solution to global poverty, increase quality of life or standard of living and increase socio economic well-being among women entrepreneur. According to Nor Aini (2008), most firms started by women are shut down in the middle of operation. Some of the causes are the mentality of this group, lacks of self-confidence, struggles to balance work and personal obligations, unable to cope with environmental issues, and nebulous in their area of expertise. There is a need for more methodological-based articles on systematic literature review (SLR) for determinants of business performance on women entrepreneur to address issues related to the lack of methodological references in SLR. For that, a total of 18 articles from 2013 through 2022 that passed the minimum quality were retrieved using systematic searching strategies. Eight main points of SLR were discussed, namely (1) the development and validation of the review protocol/publication standard/reporting standard/guidelines, (2) the formulation of research questions, (3) systematic searching strategies, (4) identification, (5) screening, (6) eligibility, (7) data extraction and (8) data demonstration.